PENGARUH TUNJANGAN KINERJA TERHADAP KINERJA PEGAWAI PADA KANTOR KECAMATAN PITUMPANUA KABUPATEN WAJO - Iwan Mamminanga; Najeminur Najeminur; Mustaqimah Mustaqimah (Jurnal Ilmu Administrasi Negara, 2023)
This research was conducted to describe the influence of performance allowances and employee performance. In addition, the general objective of this study is to analyze the influence of Performance Allowances on Employee Performance at the Pitumpanua District Office, Wajo Regency. This type of research uses a census research type with a descriptive study method. Data collection techniques used are observation, documentation, questionnaires / questionnaires. The population of this study were employees at the Pitumpanua District office, Wajo Regency. This study used descriptive data analysis techniques and inferential statistical data analysis techniques. The results of the study show that Performance Allowances and Employee Performance at the Pitumpanua District Office, Wajo Regency are included in the very good category. In addition, the Performance Allowance has a positive and significant effect on Employee Performance at the Pitumpanua District Office, Wajo Regency.